2020
DOI: 10.1371/journal.pcbi.1008069
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns of nitric oxide diffusion and degradation drive emergent cerebrovascular dynamics

Abstract: Nitric oxide (NO) is a gaseous signaling molecule that plays an important role in neurovascular coupling. NO produced by neurons diffuses into the smooth muscle surrounding cerebral arterioles, driving vasodilation. However, the rate of NO degradation in hemoglobin is orders of magnitude higher than in brain tissue, though how this might impact NO signaling dynamics is not completely understood. We used simulations to investigate how the spatial and temporal patterns of NO generation and degradation impacted d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 244 publications
(397 reference statements)
2
9
0
5
Order By: Relevance
“…It has been proposed that downregulation of cerebrovascular eNOS expression predisposes certain brain areas to lose their BBB integrity ( Soares et al, 2015 ; Al-Zaiti et al, 2018 ; Munji et al, 2019 ; Zhang et al, 2019 ; Bernstein et al, 2020 ). Intact endothelium and consequent preserved NO production in the cerebrovasculature is thus important to prevent stroke, cerebrovascular disease and neurodegeneration ( Tabatabaei and Girouard, 2014 ; Khan et al, 2019 ; Haselden et al, 2020 ). A study from a metabolic point of view concluded that Type 1 diabetes driven eNOS-deficiency increases BBB permeability ( Mayhan et al, 2015 ).…”
Section: Causes Of Arterial Stiffnessmentioning
confidence: 99%
“…It has been proposed that downregulation of cerebrovascular eNOS expression predisposes certain brain areas to lose their BBB integrity ( Soares et al, 2015 ; Al-Zaiti et al, 2018 ; Munji et al, 2019 ; Zhang et al, 2019 ; Bernstein et al, 2020 ). Intact endothelium and consequent preserved NO production in the cerebrovasculature is thus important to prevent stroke, cerebrovascular disease and neurodegeneration ( Tabatabaei and Girouard, 2014 ; Khan et al, 2019 ; Haselden et al, 2020 ). A study from a metabolic point of view concluded that Type 1 diabetes driven eNOS-deficiency increases BBB permeability ( Mayhan et al, 2015 ).…”
Section: Causes Of Arterial Stiffnessmentioning
confidence: 99%
“…This coupling between neural activity and hemodynamics is known as neurovascular coupling (NVC) [12]. While there are many successful phenomenological models of NVC [3,[13][14][15][16][17], most physiology-based models of neurovascular coupling [18][19][20][21] focus on a single cellular mechanism. As NVC is mediated through multiple processes (several molecular cascades, each mediated by different cell types), a more integrated approach is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…As shown for excitatory pyramidal neurons, geometric characteristics of an identified neuronal subpopulation are likely to differ across functionally distinct cortical areas, reflecting local properties of vertical and horizontal processing flows (Elston, 2002; Elston et al, 2006). Since NO release may affect local neurovascular dynamics (Haselden et al, 2020) in a spatially restricted zone around the dendritic field, comparing the cortical distribution and the fine morphological arrangement of dendritic arbors of NNs across distinct cortical processing fields or compartments should contribute to a better understanding of how inhibitory NNs relate to local processing circuits.…”
Section: Introductionmentioning
confidence: 99%